2017
DOI: 10.1080/07347332.2017.1320348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemotherapy on the health-related quality of life of Japanese lower rectal cancer patients after sphincter-saving surgery

Abstract: We examined the effects of adjuvant chemotherapy on the health-related quality of life (HRQOL) of lower rectal cancer patients receiving sphincter-saving surgery (SSS). In all, 109 patients completed a questionnaire before surgery and 1, 6, and 12 months afterwards. In the chemotherapy group, physical and social functioning scores were significantly lower 12 months after surgery compared with the nonchemotherapy group. These effects of adjuvant chemotherapy suggest that a different clinical approach might more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In one study, group differences in longitudinal changes in SCI were unconfirmed in a multivariate model . Five studies reported no differences in longitudinal changes in SCI between the CTX group and non‐CTX patients or healthy controls . No differences emerged in three non–breast‐cancer studies and in two studies with a follow‐up at least 1 year posttreatment .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In one study, group differences in longitudinal changes in SCI were unconfirmed in a multivariate model . Five studies reported no differences in longitudinal changes in SCI between the CTX group and non‐CTX patients or healthy controls . No differences emerged in three non–breast‐cancer studies and in two studies with a follow‐up at least 1 year posttreatment .…”
Section: Resultsmentioning
confidence: 97%
“…These modeling techniques are strong in examining the association of changing patterns of dependent and moderator variables and may provide more robust and conclusive evidence of moderating effects in the chemotherapy‐SCI relationship. Researchers also used paired t tests, repeated‐measures analysis of variance (ANOVA)/multivariate analysis of variance (MANOVA), and the nonparametric Kruskal‐Wallis test to compare mean differences of SCI at two or more time points in one or more groups. When using analytical approaches based on group means, individual variability in longitudinal changes over time may not be considered fully; mean change may be underestimated because of sample variability .…”
Section: Resultsmentioning
confidence: 99%